Evaluation of Microorganisms Electroporation Technique Efficiency in Root Canal System Sterilization: Bacterial, in Vitro Study (Journal of Hama University, 2020)
Endodontic treatment is difficult to accomplish due to multiple variables, such as the morphological and structural complexity of the root canal system (RCS), so definitive eradication of canal microorganisms is impossible, especially in infected dental pulp, resulting in unstable success rate of treatment.The aim of this study is to investigate the efficiency of Microorganisms Electroporation Technique (MET) regarding root canal system sterilization before sealing, in order to increase the success rate at long term. Recently extracted, single- and multi-rooted human teeth have been used, and divided into (8) groups according to RCS complexity and microorganisms neutralization methods. After shaping, RCS was sterilized using autoclave, followed by non-specific bacterial infection. Efficiency of bacterial neutralization of MET using pulsed current with specific criteria, were compared with traditional chemical methods (irrigation solution NaOCl, intra-canal dressing Ca(OH)2). Bacterial culture was used to quantitative evaluation of viable bacteria using Colony Forming Units (CFU) after application of studied bacterial neutralization methods.Statistical Analysis (P